Akibat Hukum Gugatan Kejaksaan Negeri Tanjung Jabung Barat Terkait Pencabutan Kekuasaan Orang Tua - Hariss, Abdul; Zulfikar, Ahmad; Rahmawati, Deska (Universitas Batanghari Jambi, 2024)
Parents are the first and foremost institution for children to receive protection, teaching and fulfillment of their rights. However, sometimes parents cannot provide protection and can even become criminals for their own biological children, as stated in the Kuala Tungkal District Court Decision Number: 01/Pid.Sus/2022/PN KLT dated 08 February 2022, which is the basis for the West Tanjung Jabung District Prosecutor's proposal. Lawsuit for Revocation of Parental Power over Children. The problem studied in this paper boils down to what are the legal consequences of the lawsuit for the revocation of parental authority over children by the Tanjung Jabung Barat District Prosecutor's Office (Study of Kuala Tungkal District Court Decision Number 16/Pdt.G/2022.PN.KLT)? The research method used is empirical juridical with interview techniques. Based on the results of research that has been carried out regarding the legal consequences of the Lawsuit for Revocation of Parental Power over Children by the West Tanjung Jabung District Prosecutor's Office as per Kuala Tungkal District Court Decision Number 16/Pdt.G/2022.PN.KLT parents whose power over children has been revoked do not have any power over the child, however the termination of this power does not necessarily sever the regional relationship between parents and children so that the parents, in this case the Defendant/Birth Father, still have the obligation to support the lives of their children.